(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2024)
ABSTRACT Background Celiac disease is an autoimmune disorder caused by eating gluten protein, which is found in some grains such as wheat, barley, and rye, which leads to an abnormal immune response that leads to intestinal inflammation. Materials and Methods The presence of the two genes was investigated in 18 samples of the samples under study, as follows (6 samples of patients), (6 samples of people suspected of being infected) and (6 samples of healthy people), at a rate of 3 males and 3 females for each group, and the groups were selected based on the results of the axis tests Immunoassay, where the DNA was extracted from the samples, its concentration and purity were measured, amplification operations were performed using the PCR technique for genes, and electrophoresis was performed. Results The results of electrophoresis after performing amplification operations using PCR technology for the genes in question showed the presence of fluorescent bands, which indicated the presence of the genes. Conclution the presence of the DQB1-0201 gene in patients with celiac disease was 100%, while the presence of the gene in suspected individuals was 66.6% compared to the control sample, which showed a gene presence of 33%. As for the presence of the DQA1-0501 gene, it was The incidence of the disease was 100% in patients with celiac disease, while the incidence of the allele in persons suspected of having the disease was 66.6% compared to healthy subjects with a frequency of 83.3%.